Kepailitan PT Asuransi Syariah Mubarakah Dan Perlindungan Peserta Dalam Konteks Peraturan Perundang-Undangan Di Indonesia - Syukron Syukron; Nurhasanah Nurhasanah (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
This article is motivated by the conflict between the participants of Mubarakah Sharia Insurance and PT Asuransi Sharia Mubarakah after the bankruptcy decision. The case of PT Asuransi Syariah Mubarakah was examined and decided by the Commercial Court. Law No. 50/2009 concerning amendments to Law No. 3/2006 concerning the Religious Courts explains that Islamic economic disputes become the absolute competence of the Religious Courts. This gap needs to be reviewed from the theory of the law of the law and the principle of Lex posterior derogat priori legi. The next problem that arises is the non-fulfillment of the rights of the insurance participants after the bankruptcy decision. this issue is analyzed using the Fiduciari Duty, Ultra Vires and piercing the corporate veil approach in the context of corporate law. This approach is used to review legal protection for insurance participants. The method used is a Nomative qualitative approach. The data used are library research and field research. There are 2 conclusions in this article, First, the bankruptcy problem is still handled by the Commercial Court due to the strength of the rule of law and the tendency of the parties and curators who have confidence in the commercial court. Second, the lack of legal protection provided to the participants of PT. Mubarakah Sharia Insurance due to lack of legal protection from the Ministry of Finance and the Financial Services Authority and the absence of rules governing insurance participants (policyholders). Losses that cause companies to go bankrupt are seen as negligence of managers to conduct business such as not complying with the level of solvency and not conducting liquidation prior to bankruptcy. Therefore, the Curator should charge and hold the Directors and commissioners accountable for paying debts to insurance participants.